ANALYZING MORPHOLOGICAL AFFIXES FOUND IN THE POETRY “THE FORERUNNER” BY KAHLIL GIBRAN - Nuri Nurmila Jamil; Indah Arvianti; Eko Heriyanto (Universitas Aki, 2022)
In the process of reading sometimes the readers have difficulty identifying the meaning of words correctly, especially words with affixes of prefixes and suffixes. The writer had made three objects of research. The first research is to find out how many affixes were used in the poetry “The Forerunner” by Kahlil Gibran, the second research is to find out what types were used in the poetry “The Forerunner” by Kahlil Gibran, the third research is to find out what types were dominant use in the poetry “The Forerunner” by Kahlil Gibran. In this study, the writer uses a descriptive mixed method that described, identified, classified, and calculated numerical data on the words of affixes found in Kahlil Gibran’s poetry. The result of the research shows the total number of affixes is 105 data found in the four chapters of the poetry “The Forerunner” by Kahlil Gibran. There are two types of affixes used in the four chapters of the poetry “The Forerunner” by Kahlil Gibran prefixes and suffixes. The dominant types of affixes found in the four chapters of the poetry “The Forerunner” by Kahlil Gibran were suffixes found in 99 data with a percentage of 94,3%.